Advanced Nanomaterials for Myocardial Ischemia-Reperfusion Injury: Bridging Precision Imaging to Targeted Therapy - Li, Jie; Shafiq, Muhammad; Yao, Minghua; Liu, Zehua; Tian, Ruizhi; Zheng, Fangqiao; Lu, Chan; Ma, Ming (China, 2026)
This review presents functional nanomaterials as integrated theranostic platforms to overcome diagnostic and therapeutic bottlenecks in myocardial ischemia-reperfusion injury (MIRI).
It highlights advances in nano-biosensors for early biomarker detection and multimodal imaging for real-time, precise diagnosis.
Key therapeutic strategies are detailed, including nanozymes for antioxidative stress, biomimetic nanocarriers for targeted delivery, and gas-releasing agents for myocardial repair.
Major translational challenges are discussed, such as low cardiac targeting efficiency, long-term biosafety, and manufacturing scalability of biomimetic systems.
Future directions emphasize smart, stimuli-responsive nanoplatforms and AI-integrated closed-loop systems for personalized cardiovascular nanomedicine.